2007
DOI: 10.1099/vir.0.83284-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Israeli acute paralysis virus, a dicistrovirus affecting honeybees in Israel: evidence for diversity due to intra- and inter-species recombination

Abstract: We report the isolation, purification, genome-sequencing and characterization of a picorna-like virus from dead bees in Israel. Sequence analysis indicated that IAPV (Israeli acute paralysis virus) is a distinct dicistrovirus. It is most homologous to Kashmir bee virus and acute bee paralysis virus. The virus carries a 9487 nt RNA genome in positive orientation, with two open reading frames separated by an intergenic region, and its coat comprises four major proteins, the sizes of which suggest alternate proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
197
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 35 publications
3
197
0
2
Order By: Relevance
“…This virus was first diagnosed in Israel, where it reportedly caused large scale honeybee mortality and symptoms included trembling wings and paralysis (Maori et al, 2007;Palacios et al, 2008). The detection of IAPV in Varroa mites sampled during this study is therefore of concern, especially since it was recently confirmed that Varroa mites are capable of transmitting IAPV to honeybees (Di Prisco et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…This virus was first diagnosed in Israel, where it reportedly caused large scale honeybee mortality and symptoms included trembling wings and paralysis (Maori et al, 2007;Palacios et al, 2008). The detection of IAPV in Varroa mites sampled during this study is therefore of concern, especially since it was recently confirmed that Varroa mites are capable of transmitting IAPV to honeybees (Di Prisco et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…Aside from the above mortality and sub-lethal effects, the symptoms associated with IAPV have not been well characterized and thus hinder our ability to observe the progression of IAPV infection in these important pollinators, especially when considering that virus-induced paralysis symptoms are normally the signal of overt infection and death. Besides, the initial observation of IAPV symptoms are from honeybees; symptom analysis in bumblebees would enhance our knowledge of this virus (de Miranda et al, 2010;DeGrandi-Hoffman & Chen, 2015;Maori et al, 2007Maori et al, , 2009Piot et al, 2015). Therefore, in this study, we report progressive viral symptoms in workers of B. terrestris, which is one of the most numerous bumblebee species in Europe (Velthuis & van Doorn, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…IAPV is positive single-stranded RNA virus in the family Dicistroviridae with a global distribution range (de Miranda et al, 2010;Maori et al, 2007;Palacios et al, 2008). The nomenclature of this virus is largely based on its symptoms that are similar to ABPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2c). Like other positive-stranded RNA viruses, the replication of IAPV (Maori et al, 2007) proceeds via the production of negative-stranded intermediates. Therefore, the presence of negative-strand RNA of IAPV in Varroa mite appears to be evidence of virus replication and suggests that the (Fig.…”
mentioning
confidence: 99%